Ansiedad, depresión, soledad y rol del cuidador de adultos mayores con enfermedad crónica - Damián Sinchiguano, Gabriela Elizabeth (2023)
ABSTRACT: The consequences of Chronic Non-Communicable Diseases represent a growing challenge for public health, given their biological, psychological, and social impact. The persistence of these conditions that do not consistently achieve cure in older adults generates the demand for secondary caregivers as an essential strategy to address the health care needs that this group of patients requires. In this context, adopting behaviors oriented toward health promotion is necessary to maintain a balance in the health-disease process. Objective: Determine the relationship between anxiety, depression, and loneliness with the adoption of the role of caregiver for older adults with NCDs treated at the Sangay Health Center, which allows proposing nursing educational actions aimed at promoting transitional care. Materials and methods A descriptive, analytical, cross-sectional, and quantitative research was developed, working with the entire study population, comprised of non-sensitive, anonymized data from 45 caregivers of older adults with NCDs. Results The presence of anxiety, loneliness, and depression in informal caregivers is identified. In this set of manifestations, concern occupied clinically significant levels, a factor that behaves negatively for adopting the role. Conclusions Family caregivers are essential for the wellbeing of people with NCDs, and their emotional health directly influences the quality of care provided. The results of this research emphasize the importance of implementing psychoemotional support interventions for caregivers, recognizing their vital contribution to the health care system.